Linking Public Health and Public Safety Data on Co-occurring Disorders Among Adults in Hawaii's Criminal Justice System. Issue 6 (November 2022) - Fontanilla, Tiana; Kim, Sunja; Bowen, Kristy; Choi, Ho Suk; Talagi, Deveraux; Fan, Victoria Y.; Borja, Vincent; Smith, Tammie; Curtis, Amy
Abstract : To better understand the behavioral health treatment needs of adults involved in the criminal justice system and to improve the continuum of services provided to this vulnerable population, Hawaii initiated a data linkage project that connects substance use and mental health data from the state Department of Public Safety with behavioral health treatment data from the state Department of Health for the State of Hawaii. Specifically, this linkage project begins to examine behavioral health treatment levels recommended by the criminal justice system and Hawaii State Hospital inpatient psychiatric admissions. We provide a preliminary summary on individuals who were both involved in the criminal justice system and received court-ordered inpatient psychiatric treatment and outline data governance procedures, future directions, and practice recommendations.